Selective electrochemical determination based on magnetic molecularly imprinted polymers for albumin detection - Leepheng, Piyawan; Limthin, Dalawan; Onlaor, Korakot; Tunhoo, Benchapol; Thiwawong, Thutiyaporn; Suramitr, Songwut; Phromyothin, Darinee (My University, 2022)
Egg allergy is one of the most common allergies in humans. Allergenic egg protein as ovalbumin is the most abundant protein found in egg white. A selective electrode in electrochemical analysis for albumin from egg white was developed based on magnetic molecularly imprinted polymers (albumin-MMIPs) modified on a screen-printed electrode. Surface modification was applied using methyl methacrylate polymer to create surface specificity for albumin protein. The modified surface was characterized by a field-emission scanning electron microscope (FE-SEM). The average pore size was obtained by Brunauer-Emmett-Teller (BET) analysis, and the potentiostat obtained all electrochemical analysis. The albumin-MMIP electrode was selectivity with albumin, comparison with gluten, glycine, casein, and glucose. The modified electrodes present selectivity of 1.13 × 104 μAg-1ml and a limit of detection of 0.18 mg ml-1. The electrode can be applied to albumin protein detection in solution form in food industries.
Keywords: albumin; electrochemical analysis; magnetic molecularly imprinted polymers (MMIPs)